Validity and reliability of the arabic version of the HLS-EU-Q16 and HLS-EU-Q6 questionnaires - Lina Bergman; Ulrica Nilsson; Karuna Dahlberg; Maria Jaensson; Josefin Wångdahl (BMC, 2023)
Abstract Background Health literacy is an important social determinant of health and affects the ability to make decisions and take action to manage one's health. The purpose of this study was to psychometrically examine the Arabic versions of HLS-EU-Q16 and HLS-EU-Q6 and their response patterns among Arabic-speaking persons in Sweden. Methods By convenience sampling from a variety of settings, a total of 335 participants were invited to participate. The participants completed a self-assessment of comprehensive health literacy by answering the Ar-HLS-EU-Q16 questionnaire, also including the six items for Ar-HLS-EU-Q6. Statistical analysis was guided by The COnsensus-based Standards for the selection of health Measurement Instruments. Floor/ceiling effects, construct, structural and criterion validity, test-retest reliability and internal consistency reliability were analysed. Results In total, 320 participants were included in the psychometric evaluation. Mean age was 42.1 (SD 12.5), 63% (n = 199) were females and 53% (n = 169) had at least 10 years of education. No floor or ceiling effect were found for the Ar-HLS-EU-Q16 or Ar-HLS-EU-Q6. For both instruments, construct validity was confirmed in four out of five expected correlations (weak positive correlation to educational level, self-perceived health, and years in Sweden; moderate positive correlation with higher sum score on the Arabic electronic health literacy scale, and strong positive correlation to higher Ar-HLS-EU-Q16/Ar-HLS-EU-Q6). For Ar-HLS-EU-Q16, the principal component analysis resulted in a three-factor model with all items significantly correlating to only one factor. For Ar-HLS-EU-Q6, the principal component analysis supported a one-factor solution. Criterion validity showed poor agreement between the two questionnaires with a Cohen κ 0.58 (p < 0.001). Test-retest reliability showed a substantial agreement, Cohen's κ for Ar-HLS-EU-Q16 and Ar-HLS-EU-Q6 were both 0.89. The internal consistency of both versions was acceptable, Cronbach alpha for Arabic-HLS-EU-Q16 was 0.91 and for Arabic-HLS-EU-Q6, 0.79. Split-half reliability was 0.95 and 0.78, respectively. Conclusion The Arabic version of HLS-EU-Q16 shows good psychometric properties, validated in a Swedish setting. The findings can further inform and guide future validation studies in other settings worldwide. Furthermore, the results of the present study did not support criterion validity of Ar-HLS-EU-Q6.